Olefin metathesis in air - Piola, Lorenzo; Nahra, Fady; Nolan, Steven P. (Beilstein Journal of Organic Chemistry, 2015)
Since the discovery and now widespread use of olefin metathesis, the evolution of metathesis catalysts towards air stability has become an area of significant interest. In this fascinating area of study, beginning with early systems making use of high oxidation state early transition metal centers that required strict exclusion of water and air, advances have been made to render catalysts more stable and yet more functional group tolerant. This review summarizes the major developments concerning catalytic systems directed towards water and air tolerance.
Keywords: air stability; catalysis; olefin metathesis; RCM; ROMP; ruthenium